Pharmacological and non-pharmacological countermeasures to Space Motion Sickness: a systematic review - Khalid, Akil; Prusty, Pragnya P.; Arshad, Iqra; Gustafson, Hannah E.; Jalaly, Isra; Nockels, Keith; Bentley, Barry L.; Goel, Rahul; Ferrè, Elisa R. (Frontiers in Neural Circuits, 2023)
Space Motion Sickness (SMS) is a syndrome that affects around 70% of astronauts and includes symptoms of nausea, dizziness, fatigue, vertigo, headaches, vomiting, and cold sweating. Consequences range from discomfort to severe sensorimotor and cognitive incapacitation, which might cause potential problems for mission-critical tasks and astronauts and cosmonauts’ wellbeing. Both pharmacological and non-pharmacological countermeasures have been proposed to mitigate SMS. However, their effectiveness has not been systematically evaluated. Here we present the first systematic review of published peer-reviewed research on the effectiveness of pharmacological and non-pharmacological countermeasures to SMS. We performed a double-blind title and abstract screening using the online Rayyan collaboration tool for systematic reviews, followed by a full-text screening. Eventually, only 23 peer-reviewed studies underwent data extraction. Results indicate that pharmacological and non-pharmacological countermeasures can both help mitigate SMS symptoms. However, no definitive recommendation can be given regarding the superiority of any particular countermeasure approach. Importantly, there is considerable heterogeneity in the published research methods, lack of a standardized assessment approach, and small sample sizes. To allow for consistent comparisons between SMS countermeasures in the future, standardized testing protocols for spaceflight and ground-based analogs are needed. We believe that the data should be made openly available, given the uniqueness of the environment in which it is collected.